Analysis of the Serotonergic System in a Mouse Model of Rett Syndrome Reveals Unusual Upregulation of Serotonin Receptor 5b - Vogelgesang, Steffen; Niebert, Sabine; Renner, Ute; Möbius, Wiebke; Hülsmann, Swen; Manzke, Till; Niebert, Marcus (Frontiers in Molecular Neuroscience, 2017)
Mutations in the transcription factor methyl-CpG-binding-protein 2 (MeCP2) cause a delayed-onset neurodevelopmental disorder known as Rett syndrome (RTT). Although alteration in serotonin levels have been reported in RTT patients, the molecular mechanisms underlying these defects are not well understood. Therefore, we chose to investigate the serotonergic system in hippocampus and brainstem of Mecp2-/y knock-out mice. The serotonergic system in mouse is comprised of 16 genes, whose mRNA expression profile was analyzed by quantitative RT-PCR. Mecp2-/y mice are an established animal model for RTT displaying most of the mental and physical impairments of human patients and the selected areas receive significant modulation through serotonin. Using anatomically and functional characterized areas, we found region-specific differential expression between wild type and Mecp2-/y mice at post-natal day 40. In brainstem, we found 5 genes to be dysregulated, while in hippocampus, 2 genes were dysregulated. The one gene dysregulated in both brain regions was dopamine decarboxylase, but of special interest is the serotonin receptor 5b (5-ht5b), which showed 75-fold dysregulation in brainstem of Mecp2-/y mice. This dysregulation was not due to upregulation, but due to failure of down-regulation in Mecp2-/y mice during development. Detailed analysis of 5-ht5b revealed a receptor that localizes to endosomes and interacts with Gαi proteins.